A prospective study of clinical profile, epidemiology and etiological diagnosis of corneal ulcer in North-West Rajasthan - Joshi, Rashmi Kewaliya; Goyal, Rekha Kumari; Kochar, Anju (International Journal Of Community Medicine And Public Health, 2017)
Background: To determine clinical profile, epidemiological and etiological diagnosis of corneal ulcer in North-West Rajasthan. Methods: One hundred thirty three patients who were treated for corneal ulcer were enrolled in this study from February 2015 to May 2017. The historical aspect including symptoms, duration of ulcer and relevant local and systemic predisposing factor and detailed ocular examination were noted. Corneal scrapings were taken up in almost all cases except few cases and sent for microbiological assessment. Results: 66.9% were males and 33.08% females. Most common age group was between 30-60 years and majority of patients were from rural areas. Most common pathogen was found Aspergillus fumigatus. Conclusions: Corneal ulcer was seen predominantly in males of 30-60 years of age of rural background. Aspergillus fumigatus being most common etiological organism.